2022
DOI: 10.1063/5.0097596
|View full text |Cite
|
Sign up to set email alerts
|

Shock-driven dispersal of a corrugated finite-thickness particle layer

Abstract: A research area emerging in the multiphase flow community is the study of shock-driven multiphase instability (SDMI), a gas–particle analog of the traditional fluid-fluid Richtmyer–Meshkov instability (RMI). In this work, we study the interaction of planar air shocks with corrugated glass particle curtains through the use of numerical simulations with an Eulerian–Lagrangian approach. One objective of this study is to compare the simulated particle curtains to a comparable set of shock tube experiments performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…planar, cylindrical and spherical geometries) and reshocks have different and significant influences on the hydrodynamic instabilities of the multiple interfaces (Mikaelian 1996, 2005; de Frahan, Movahed & Johnsen 2015; Li, Samtaney & Wheatley 2018; Qiao & Lan 2021; Ouellet et al. 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…planar, cylindrical and spherical geometries) and reshocks have different and significant influences on the hydrodynamic instabilities of the multiple interfaces (Mikaelian 1996, 2005; de Frahan, Movahed & Johnsen 2015; Li, Samtaney & Wheatley 2018; Qiao & Lan 2021; Ouellet et al. 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the initial perturbations of the two interfaces, the number of interfaces, the geometry of the computational domain (i.e. planar, cylindrical and spherical geometries) and reshocks have different and significant influences on the hydrodynamic instabilities of the multiple interfaces (Mikaelian 1996(Mikaelian , 2005de Frahan, Movahed & Johnsen 2015;Li, Samtaney & Wheatley 2018;Qiao & Lan 2021;Ouellet et al 2022).…”
Section: Introductionmentioning
confidence: 99%